2018
DOI: 10.3928/00220124-20180417-06
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Preceptor Training on New Graduate Registered Nurse Transition Experiences and Organizational Outcomes

Abstract: A variety of positive outcomes can be realized for NGRNs who partner with formally trained preceptors. J Contin Educ Nurs. 2018;49(5):216-220.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…As new graduate registered nurses adjust to the workplace, their colleagues play a vital role in helping them feel psychologically safe. Of these colleagues, research suggests preceptors play a particularly critical role in helping new graduate registered nurses successfully transition to practice (Goss, 2015; Piccinini, Hudlun, Branam, & Moore, 2018). In this study, new graduate registered nurses reported feeling more psychologically safe when they viewed themselves as credible and trusted by their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…As new graduate registered nurses adjust to the workplace, their colleagues play a vital role in helping them feel psychologically safe. Of these colleagues, research suggests preceptors play a particularly critical role in helping new graduate registered nurses successfully transition to practice (Goss, 2015; Piccinini, Hudlun, Branam, & Moore, 2018). In this study, new graduate registered nurses reported feeling more psychologically safe when they viewed themselves as credible and trusted by their colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…The initiative has been evaluated through secondary data, focus groups, and interviews, showing success in stimulating new employment and retention of nurses. Nurses were pleased with immediate hiring and mentorship and decreased their considerations of emigration [49,50,52].…”
Section: Financing Hrhmentioning
confidence: 99%
“…The DEU as a preceptor training model for clinical site/academia partnership is one strategy that can close the gap between clinical practice and tertiary education (Mitchell et al, 2018). Evidence also shows that preceptor training enhances the students' transition to practice (Piccinini, Hudlun, Branam, & Moore, 2018).…”
Section: Discussion Between Clinical Leaders and Nursing Faculty Unementioning
confidence: 99%
“…Preceptors can be given the resources needed to be successful in their role, potentially resulting in successful clinical experiences for the nursing student and preceptor, however, there is lacking information about how to do so (Piccinini et al, 2018). This innovative concept is a way to enrich the experience of nursing students in roles within public health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation